Advancing understanding of influences on cervical screening (non)‐participation among younger and older women: A qualitative study using the theoretical domains framework and the COM‐B model - Bernadine O'Donovan (Wiley, 2021)
Abstract Background Effective screening can prevent cervical cancer, but many women choose not to attend their screening tests. Objective This study aimed to investigate behavioural influences on cervical screening participation using the Theoretical Domains Framework (TDF) and COM‐B models of behaviour change. Design A qualitative study and semistructured phone interviews were conducted with women invited for routine screening tests within the national cervical screening programme in Ireland. Setting and Participants Forty‐eight women aged 25–65 years were recruited from the national screening register. Results Seven core themes were identified that mapped to three COM‐B components and 11 TDF domains: (1) knowledge of cervical cancer and screening, (2) coping with smear tests, (3) competing motivational processes—automatic and reflective, (4) cognitive resources, (5) role of social support, (6) environmental influences and (7) perceputal and practical influences. A range of knowledge about screening, perceived risk of cervical cancer and human papillomavirus infection was evident. Factors that influenced screening behaviours may be hierarchical—some were assigned greater importance than others. Positive screening behaviours were linked to autonomous motivation. Deficits in physical and psychological capability (inadequate coping skills) were barriers to screening, while physical and social opportunity (e.g. healthcare professional ‘champions’) could facilitate participation. Older women raised age‐related issues (e.g. screening no longer necessary) and had more negative attitudes to screening, while younger women identified practical barriers. Conclusions This study provides insight into screening participation and will aid development of theoretically informed interventions to increase uptake. Patient or Public Contribution Women invited for screening tests through the national screening programme were interviewed. A Public & Patient Involvement (PPI) Panel, established to provide input into all CERVIVA research projects, advised the research team on recruitment materials and were given the opportunity to review and comment on the interview topic guide. This panel is made up of six women with various cervical screening histories and experiences.